Mortality Reporting Management in Electronic Medical Recprd at Hospital X - Arimbi Ulfa Nazira; Achmad Jaelani Rusdi; Untung Slamet Suhariyono (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2024)
Mortality reporting is an important aspect of evaluating the quality of health services. At Hospital X, the still manual mortality reporting system faces challenges such as slow processes and vulnerability to errors, therefore this study aims to analyze the input, process, and output in mortality reporting. The method used in this study uses a qualitative approach with interview and observation techniques, data were collected from medical record and administrative staff involved in the mortality reporting process, as well as analysis of related documents. The results of this study indicate that the implementation of electronic medical records has increased efficiency in mortality reporting. However, data accuracy is still a significant problem caused by data input errors and lack of training for system users. These research findings indicate that ongoing training and improved technology infrastructure are essential to support the EMR system at Hospital X. With an optimal ERM system, it is expected that the quality of mortality reporting will improve, which will later have an impact on improving the overall quality of health services. This study recommends further development in the management of mortality reporting using EMR